Predictors Associated With Post-Traumatic Hydrocephalus in Patients With Head Injury Undergoing Unilateral Decompressive Craniectomy - Hu, Qianxin; Di, Guangfu; Shao, Xuefei; Zhou, Wei; Jiang, Xiaochun (Frontiers in Neurology, 2018)
Objective Post-traumatic hydrocephalus (PTH) makes recovery from head trauma after decompression more complicated and is associated with high risks of clinical deterioration and poor outcomes. The aim of this study was to verify the predictors associated with the development of PTH in patients with head injury undergoing unilateral decompressive craniectomy (DC). Methods Among traumatic brain injury (TBI) patients who underwent unilateral DC between January 2013 and December 2016, the clinical medical records, radiological information, and changes of patients’ conditions in the 3-month after injury were reviewed retrospectively. Results 183 TBI patients after unilateral DC were analyzed, and 50 (27.32%) of them suffered PTH based on head CT scans. Univariate and multivariable analyses revealed that older age (p = 0.002), the Glasgow Coma Scale (GCS) score at admission (p < 0.001), intraventricular hemorrhage (IVH; p = 0.008), post-traumatic cerebral infarction (PCI; p = 0.007), and postoperative meningitis (p = 0.016) were independent predictors for the hydrocephalus after DC. Receiver operating characteristic curves were created and the area under the curve (AUC) were calculated to further assess the accuracy of the variables for predicting PTH. The AUC was 0.836 for the combined all five independent factors (95% confidence interval: 0.775–0.887). Conclusion TBI patients who undergo unilateral DC with advanced age, lower GCS score at admission, coexisting IVH, PCI, and/or postoperative meningitis should be closely monitored at follow-up assessments for earlier prediction of PTH.